Tindakan Menempati Rumah Tanpa Hak Ditinjau Berdasarkan Pasal 167 Kitab Undang-Undang Hukum Pidana - Yohanes Anugrah Wibowo (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2021)
Criminal law in Indonesia as a public law regulated in the Criminal Code. In the Criminal Code is a general rule regarding the rules of crime in Indonesia, therefore it becomes a guideline for the rules of crime that apply specifically. One example is the Law on Housing and Settlement, which is a special regulation and opposes its penalties, which will change these rules as special rules and regulations in the law that will be regulated in the Criminal Code. The application of the law on land and housing issues in practice is an inaccurate application of the law. This is not related to laws and regulations that oppose the application of law by law enforcers and changing developments for the sake of changes to the laws and regulations in Indonesia. Keywords: crime, land crime, housing crime.